Wiesław Jamrożek (1954-2021) jako kierownik Zakładu Historii Wychowania Wydziału Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu. Wspomnienie w 70. rocznicę urodzin - Brenk, Mikołaj; Nowak-Kluczyński, Konrad (Studia Edukacyjne, 2024)
The article presents Prof. Wiesław Jamrożek, an outstanding historian of education who died prematurely on April 2, 2021, head of the Department of History of Education at the Faculty of Educational Studies at Adam Mickiewicz University, Poznań. The authors recall Wiesław Jamrożek’s academic journey from a student of pedagogy to the head of the Department along with the acquisition of successive academic degrees. They focus on his activities and achievements as organizer, supervisor, and educator. They note the respect and continuation of the ides of his predecessors, Jan Hellwig and Stanisław Michalski.